2001
DOI: 10.1095/biolreprod64.3.879
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Events Are Differently Mediated by Microfilaments, Microtubules, and Mitogen-Activated Protein Kinase During Porcine Oocyte Maturation and Fertilization In Vitro1

Abstract: The role of microfilaments, microtubules, and mitogen-activated protein (MAP) kinase in regulation of several important dynamic events of porcine oocyte maturation and fertilization is described. Fluorescently labeled microfilaments, microtubules, and cortical granules were visualized using either epifluorescence microscopy or laser scanning confocal microscopy. Mitogen-activated protein kinase phosphorylation was revealed by Western immunoblotting. We showed that 1) microfilament disruption did not affect mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 44 publications
8
106
0
Order By: Relevance
“…These observations suggest that the cytoskeletal architecture of the oocyte may alter irreversibly during the intrafollicular development, affecting the ability of the oocyte to become mature and fertilized, although gilts of a similar age were immature. Further, the high incidence of decreased cortical microfilaments could account for the decreased rate of PBII expulsion in the denuded (grade 4) oocytes, because microfilaments are required for cytokinesis (Sun et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations suggest that the cytoskeletal architecture of the oocyte may alter irreversibly during the intrafollicular development, affecting the ability of the oocyte to become mature and fertilized, although gilts of a similar age were immature. Further, the high incidence of decreased cortical microfilaments could account for the decreased rate of PBII expulsion in the denuded (grade 4) oocytes, because microfilaments are required for cytokinesis (Sun et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm aster enlarged during sperm head decondensation and extended throughout the cytoplasm during PN formation (Kim et al, 1996c(Kim et al, , 1997b. Recent reports describe the origin of the active microtubule-organizing center as paternally derived and its role in PN migration and apposition (Kim et al, 1996c(Kim et al, , 1997bSun et al, 2001). In monospermic zygotes, the male and female PN were included in two different domains of microtubules, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was reported that the microfilament modulator JAS inhibited sperm incorporation and prevented cortical granules (CG) exocytosis in murine oocytes (Terada et al, 2000). In murine oocytes, pronucleus migration is blocked upon inhibition of microfilament assembly (Schatten et al, 1989;Terada et al, 2000), while in pigs (Sun et al, 2001a) or urchins (Schatten et al, 1992), microtubule assembly is not required for pronucleus formation. During fertilization in sea urchins, pigs, cattle and humans, sperm introduces the centrosome into the egg.…”
Section: Strengths and Disadvantages Of Porcine Oocyte Modelmentioning
confidence: 93%
“…Several studies have reported that fertilization of pig oocytes resembles more that of lower vertebrates than mice (Long et al, 1993;Sun et al, 2001a). In sea urchin, starfish, porcine or bovine oocytes, sperm interaction with the oocyte or their penetration is impaired by microfilament inhibitors (Schatten et al, 1982).…”
Section: Strengths and Disadvantages Of Porcine Oocyte Modelmentioning
confidence: 99%